Chloride Ion Penetration Resistance of Reactive Powder Concrete with Mineral Admixtures - Xinmin YU; Hongji ZHANG; Dehong WANG; Yanzhong JU; Mengxin KANG; Yidan MA (Medžiagotyra, 2024)
This study employed the rapid chloride ion penetration test and the salt spray erosion method to examine electric flux changes in mineral-admixed reactive powder concrete (RPC). Variations in the chloride ion content and diffusion coefficient under different erosion durations and depths were also investigated. The impact of mineral admixtures on the chloride penetration resistance was explored. Notably, after mixing fly ash (FA) and granulated blast furnace slag (GGBS), the electric flux values of RPC of each group were significantly reduced, and the electric flux values of RPC of the mixed group were significantly lower than those of the single mixed group and the reference group, in which the electric flux of FA10G10 was reduced by 85.2% compared to the control group; at the same erosion cycle and depth, the chloride ion content and diffusion coefficient of the mixed group were significantly lower than the control group. It shows that the reasonable compounding of mineral admixtures can better exert the "superposition effect", improve the compactness inside the matrix, and effectively reduce the chloride ion penetration rate. Considering comprehensively, the FA10G10 group has the best chloride penetration ion resistance effect.